The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12905-021-01321-5
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with simultaneous use of contraception and the vaginal ring for HIV prevention in sub-Saharan Africa

Abstract: Background Clinical trials have found that a monthly dapivirine vaginal ring was well-tolerated and reduced HIV-1 risk among women in sub-Saharan Africa. However, in order for the ring or other novel prevention methods to have optimal impact, it is necessary to understand and address women’s challenges to uptake and adherence. This paper provides insight into a few key challenges noted by women using the ring and contraceptives simultaneously. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…As other studies have shown, some participants reported negative experiences following menses suppression with a preference in non-suppression (13,18,22). Similar to these studies, we found that menstrual suppression caused worry, fear, and anxiety about unintended pregnancies, among negative health outcomes like infections, hormonal imbalances, and cancer.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…As other studies have shown, some participants reported negative experiences following menses suppression with a preference in non-suppression (13,18,22). Similar to these studies, we found that menstrual suppression caused worry, fear, and anxiety about unintended pregnancies, among negative health outcomes like infections, hormonal imbalances, and cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Following pregnancy tests and a doctor's confirmation of no underlying health issues, the majority of participants felt at ease. However, like other studies (13,16,18,19,22), a few participants had persistent fear and anxiety whenever they missed menses, and uncertainty about when they expected menses disincentivizing them from NuvaRing use. These negative experiences may be associated with existing literature ( 16) that the community regarded women without menses as pregnant or infertile, abnormal, bewitched, or unhealthy.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations